PERLINDUNGAN HUKUM BAGI NARAPIDANA DENGAN MASALAH KESEHATAN MENTAL DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Hadini, La Ode Muhammad Aldhian Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study examines the legal protection of inmates with mental health issues in correctional facilities. The urgency of this research arises from the increasing recognition of mental health as a critical aspect of human rights within the penal system. Utilizing a normative legal research method, the study analyzes existing laws and regulations, as well as their implementation in prisons. The findings indicate significant gaps in legal protections and inadequate mental health services for inmates, highlighting the need for comprehensive reforms. The study concludes that enhancing legal frameworks and mental health support systems is essential to safeguard the rights of vulnerable inmates and promote rehabilitation.Keywords: legal protection; mental health; inmates; correctional facilities; human rights.